2007
DOI: 10.1002/mnfr.200700213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of the effects of olive oil and other dietary lipids on cancer

Abstract: Cancer is one of the main causes of mortality worldwide. Geographical differences in incidence rates suggest a key effect of environmental factors, especially diet, in its aetiology. Epidemiologic and experimental studies have found a role of dietary lipids in cancer, particularly breast, colorectal, and prostate cancers. Their incidence in the Mediterranean countries, where the main source of fat is olive oil, is lower than in other areas of the world. Human studies about the effects of dietary lipids are lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 107 publications
8
106
1
Order By: Relevance
“…In the absence of such a study, there is still well-documented evidence of the beneficial effects of the diet consistent with an increased understanding of the mechanisms by which components of this diet act in an integrated manner within a matrix of molecules to mitigate risk factors. Recognition of its benefits may well lead to the Mediterranean diet becoming an indispensible part of a healthy lifestyle [78,79].…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of such a study, there is still well-documented evidence of the beneficial effects of the diet consistent with an increased understanding of the mechanisms by which components of this diet act in an integrated manner within a matrix of molecules to mitigate risk factors. Recognition of its benefits may well lead to the Mediterranean diet becoming an indispensible part of a healthy lifestyle [78,79].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been repeatedly suggested that the ability of the so-called 'Mediterranean diet' (MD) (i.e., the dietary patterns found in olive-growing areas of the Mediterranean basin) to significantly reduce the risk of several types of human carcinomas including breast cancer (36)(37)(38)(39), can be largely attributed to the unique healthy characteristics of EVOO, an integral ingredient of the traditional MD. Although these findings might suggest that, in the future, the use of supplements derived from EVOO will be a useful strategy for the prevention and/or treatment of cancer, both the specific components and the specific molecular mechanisms that exert EVOO-related anti-carcinogenic effects have not yet been thoroughly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects may be due to the main MUFA in olive oil, oleic acid, and to certain minor compounds such as squalene and phenolic compounds [82]. Recent studies have also shown that canola oil, with high MUFA, oleic acid, can decrease colon and breast cancer incidence significantly [83,84].…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%